Cross-border Cooperation in Czech-German Non-profit Organizations - Kuthanová, Kateřina (Jihočeská univerzita, 2019)
This thesis examines Czech-German cross-border cooperation within intercultural communication, identifies problems and develops possible solutions. The thesis is divided into a practical and a theoretical part. The theoretical part first describes the Czech-German cross-border cooperation and then intercultural communication, followed by a discussion of the context and the research methods. In the practical part, the author first performs a sequential analysis of data collected via interviews conducted with people working in the Tandem organization. The results of the analysis are interpreted, problems within the cooperation of Tandem are identified, and possible solutions developed. A glossary divided into two parts, recapitulating the definitions of relevant terms from the first two theoretical chapters of this thesis, is listed at the end of this work. A French résumé summarizing all the important points and conclusions is enclosed with the thesis. The aim of this thesis is to answer the following research question: "Linguistic and intercultural challenges of Czech-German non-profit cross-border cooperation: The case of the Tandem organization."
Cross-border Cooperation in Czech-German Non-profit Organizations
Keywords: Cross-border cooperation; non-profit organizations; intercultural communication; Cross-border cooperation; non-profit organizations; intercultural communication